Komparasi Metode K-NN Dan K-Means Untuk Klasifikasi Buah Mangga - Apriani, Apriani; Himamunanto, A. R.; Budiati, Haeni (STMIK Banjarbaru, 2024)
This Research aim of comparing the modified K-means method for classification processing of training models (Supervised) with the K-NN method using the Mango Arumanis, Golek, Madu and Gedong classes. Feature extraction used in processing classification methods is based on shape characteristics consisting of metric and eccentricity. The research results obtained that the percentage precision of the K-NN method was Arumanis: 0.9%, Madu: 0.9%, Gedong: 0.9%, Golek: 0.8%, and the K-Means method was Arumanis: 0.7%, Honey: 0.9%, Gedong: 0.9%, Golek 0.6%. The recall percentage of the K-NN method is Arumanis: 0.90%, Madu: 0.75%, Gedong: 1.00%, Golek: 0.89% and the K-means method is Arumanis: 0.70%, Madu: 0 .64%, Gedong: 1.00%, Golek: 0.86%. The accuracy percentage of the K-NN classification method is Arumanis: 94.59%, Madu: 89.74%, Gedong: 97.22%, Golek: 92.11% and the K-Means method is Arumanis: 83.78%, Madu: 83.78%, Gedong: 96.88%, Golek: 86.11%. For global precision, recall and accuracy values, the K-NN method is greater than the K-Means method. Thus, the K-Means classification method which was modified to use supervised training data is still not as good as the K-NN method in classifying mango fruit types. It is hoped that the accuracy of the method for classifying mango fruit plant types by extracting shape characteristics can obtain uniform shape quality.Keywords: Image Processing; Feature Extraction; K-means, K-NN; Metric, EccentricityAbstrakPenelitian dengan tujuan komparasi Metode K-means yang dimodifikasi untuk pemrosesan klasifikasi model pelatihan (Supervised) dengan MetodeK-NN mempergunakan kelas Mangga Arumanis, Golek, Madu dan Gedong. Ekstraksi ciri yang dipergunakan dalam pemrosesan metode klasifikasi berdasarkan ciri bentuk yang terdiri dari metric dan eccentricity. Hasil penelitian memperoleh presentase precision metode K-NN adalah Arumanis: 0,9%, Madu: 0,9%, Gedong: 0,9%, Golek: 0,8%, dan metode K-Means adalah Arumanis: 0,7%, Madu: 0,9%, Gedong: 0,9%, Golek 0,6%. Presentase recall metode K-NN adalah Arumanis: 0,90%, Madu: 0,75%, Gedong: 1,00%, Golek: 0,89% dan metode K-means adalah Arumanis: 0,70%, Madu: 0,64%, Gedong: 1,00%, Golek: 0,86%. Presentase Accuracy metode klasifikasi K-NN adalah Arumanis: 94,59%, Madu: 89,74%, Gedong: 97,22%, Golek: 92,11% dan metode K-Means adalah Arumanis: 83,78%, Madu: 83,78%, Gedong: 96,88%, Golek: 86,11%. Untuk nilai precision, recall dan accuracy secara global adalah metode K-NN lebih besar daripada metode K-Means. Dengan demikian, metode klasifikasi K-Means yang dimodifikasi untuk dapat mempergunakan data pelatihan (supervised) masih belum mampu sebaik Metode K-NN dalam klasifikasi jenis buah mangga. Diharapkan akurasi metode klasifikasi jenis tanaman buah mangga dengan ekstraksi ciri bentuk dapat memperoleh kualitas bentuk yang seragam.Kata kunci: Pengolahan Citra, Ekstraksi Ciri, K-means, K-NN, Metric, Eccentricity